Impact of functional re-education and environmental adaptation in cancer patients with respiratory pathology: Study protocol - Eduardo Jose Fernandez-Rodriguez; Maria Isabel Rihuete-Galve; Alberto Garcia-Martin; Celia Sanchez-Gomez; Fausto Jose Barbero-Iglesias; Roberto Mendez-Sanchez; Ana Silvia Puente-Gonzalez; Susana Saez-Gutierrez; Emilio Fonseca-Sanchez; Juan Jesus Cruz-Hernandez (PLoS ONE, 2025)
Background In recent years, cancer survival rates have increased exponentially. However, this rise in survival comes with a significant drawback. As the number of treatment lines has grown, so too have the side effects, which can severely impact patients’ functionality and quality of life. One of the most concerning effects is dyspnoea, a serious health issue that imposes substantial limitations on individuals. While traditional clinical approaches, primarily focused on pharmacological interventions, are commonly employed to manage dyspnoea, we argue that these methods may not always provide optimal symptomatic relief. Therefore, we propose a study protocol to implement an interdisciplinary intervention for these patients. This protocol aims to enhance standard clinical practice by introducing a program of functional re-education and environmental adaptation. We believe this intervention is essential for the follow-up care of patients with respiratory conditions after hospital discharge. Methods A two-arm, randomized, parallel, controlled clinical trial will be conducted by the University of Salamanca, Spain, in collaboration with the Medical Oncology Service of the University Health Care Complex of Salamanca. The trial aims to recruit 80 oncology patients who exhibit symptoms of dyspnoea during hospital admission. Participants will be randomly assigned to one of two groups: the control group, which will receive a health education program, and the experimental group, which will receive both the health education program and a functional re-education and environmental adaptation program. Assessments will be conducted at three time points: baseline (prior to hospital discharge), follow-up (15 days after discharge), and the end of the intervention (1 month after discharge). During these assessments, sociodemographic data will be collected, and the following scales will be administered: Barthel Index, Medical Research Council Dyspnoea Scale (mMRC), EuroQol 5-D questionnaire (EQ-5D), Visual Analogue Scale (VAS), Short Physical Performance Battery (SPPB), Tampa Scale for Kinesiophobia (TSK), and the Zarit Reduced Caregiver Burden Scale. Discussion The findings of this research can be easily implemented in clinical settings by introducing a targeted intervention to improve the quality of life for this patient population. This study aims to advance traditional clinical approaches by facilitating the recovery or adaptation of cancer patients in their daily routines, in relation to the severity of their symptoms. Our primary goal is to enhance independence and functionality, ultimately improving their overall standard of living. Trial registration ClinicalTrials.gov; ID: NCT06035263. Registered on: September 19, 2023. https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000DM2U&selectaction=Edit&uid=U0004OJ7&ts=6&cx=f7qqxo.